Engines of Inequality: Class, Race, and Family Structure - Wax, Amy L. (2008)
The past 30 years have witnessed a dramatic divergence in family structure by social class, income, education, and race. This article reviews the data on these trends, explores their significance, and assesses social scientists’ recent attempts to explain them. The article concludes that society-wide changes in economic conditions or social expectations cannot account for these patterns. Rather, for reasons that are poorly understood, cultural disparities have emerged by class and race in attitudes and behaviors surrounding family, sexuality, and reproduction. These disparities will likely fuel social and economic inequality and contribute to disparities in children’s life prospects for decades to come